Azimuthally invariant phase tomography of optically anisotropic sections of biological tissues - Sidor, M.I.; Karachevtsev, A.O.; Prysyazhnyuk, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Considered in this work is the theoretical background of the azimuthally stable method of Jones matrix mapping applied to histological sections of uterine neck biopsy based on spatial-frequency selection of the mechanisms responsible for linear and circular irefringence. The comparative results of measuring the coordinate distributions of the complex degree of mutual anisotropy formed by fibrillar networks of myosin and collagen fibrils of uterine neck tissue being in different pathological states – pre-cancer (dysplasia) and cancer (adenocarcinoma) – have been shown. The values and ranges of the change in the statistical (moments of the 1st to 4 th orders) parameters of the complex degree of mutual anisotropy of coordinate distributions have been studied. The objective criteria for diagnostics of pathology and differentiation of its severity degree have been determined.